Sustainable Strategic Directions of Regional Development in Romania in the Context of European Integration - Cristina Gabriela Dumitru; Andrei-Marius Sandru (CES Working Papers, 2015)
Sustainable development represents an equitable development model for which the main concern is achieving a balance between economic growth and raising the quality of life through the use of natural resources within the planet's tolerable limits. The sustainable development of community spaces is in the pursuit of preserving the right to access resources for future generations through their equitable use, keeping the excavation rate lower than the regeneration rate for renewable resources, and the excavation rate of non-renewable resources not exceeding their substitution rate. On the other hand, regional development implies the diversification of economic activities by supporting investments in the private sector with the purpose of lowering the unemployment rate towards increasing quality of life using different measures in field like: developing the small and medium-sized enterprises sector, the transfer of knowledge and education, rural development, quality of the surrounding environment, health and infrastructure. The regional development policy encourages the stimulation of a balanced growth of our territory by lowering the existing imbalance between regions at the current moment and by reducing the possibility for it to appear. Furthermore, the regional and rural growth of Romania in the context of sustainable development is a short term process. Due to the specificity of Romanian agriculture, predominantly subsistence farming, the inadequate structure and main factor that limits agricultural competitive growth, it implies a closer look over the social sector. Therefore, two major action plans are asserted, firstly developing connective activities in the rural space and the integration into the labour market of the people engaged into agriculture, and secondly the growth of agribusinesses by supporting measures that target the creation of associations towards increasing the efficiency of Romanian agriculture.
Keywords: O2; Q0; 330; Jewish building; heritage of Transylvania; transnational dialogue; identity; globalisation problems